One AI or Many? - Papert, Seymour (Daedalus: Journal of the American Academy of Arts & Sciences)
Discusses some issues about the nature of artificial intelligence and its appeal to people more interested in the human mind than in building robots. Presentation of connectionism as behaviorism in the computer field; Important role of parallel supercomputers in the connectionist revival; Introduction of the concept of distributed neural network.